Pengaruh Religiusitas Dan Literasi Keuangan Syariah Mahasiswa Terhadap Minat Menjadi Nasabah Di Bank Syariah : (Studi Kasus Mahasiswa Program Studi Perbankan Syariah UMSU) - Lubis, Tarisya Ativya; Khairunnisa, Khairunnisa (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
With a high level of religiosity, individuals can understand that saving in an Islamic bank is not only beneficial on an individual level but also contributes to the welfare of the Muslim community. Financial literacy, especially in the context of Shariah finance, significantly influences the tendency to conduct transactions or use products in Islamic banking. However, Shariah financial literacy among students is still considered less important, as they tend to prioritize personal consumption over long-term financial considerations. This study aims to explore the influence of religiosity and Shariah financial literacy on students' willingness to save funds in Islamic banks, providing detailed insights into the aspects affecting financial decision-making among students. The study employs a quantitative approach with a population of 190 students and uses 66 samples selected through random sampling. The study's findings indicate that religiosity partially and significantly affects customer interest, as evidenced by the religiosity t-value being greater than the t-table value (3.388 > 1.996). Similarly, Shariah financial literacy significantly impacts customer interest, with its t-value also exceeding the t-table value (8.386 > 1.996). The F-value is greater than the F-table value (109.894 > 2.76), with a significance level of 0.001, which is lower than 0.05, indicating that both religiosity and Shariah financial literacy together significantly impact customer interest, accounting for 77.7% of the influence, while the remaining 22.3% is influenced by other factors. These findings contribute to a better understanding of how religiosity and Shariah financial literacy influence students' interest in becoming customers of Islamic banks.